Overseas Filipinos' remittance behavior - Edita A. Tan (University of the Philippines, School of Economics (UPSE), 2006)
An estimated 9 million Filipinos, about 10% of the population, now reside abroad as permanent immigrants in advanced economies and as temporary migrant workers. The permanent immigrants who are mostly in the US, Australia and Canada comprise about 45% of the total. The migrant workers are employed in varied occupations in very varied destinations encompassing all the world continents. The migrants' remittances have contributed greatly to GNP and foreign exchange earnings averaging 6-7% and 20%, respectively, over the past decade. The paper analyzes the migrants' remittance behavior using individual observations from an Asian Development Bank 2004 survey of vacationing migrants. The paper assumes altruism to be the principal motivation for remitting foreign income and finds empirical support from the data. A two-stage regression model that estimates the effect of predicted foreign income, immigration status, (permanent immigrant or temporary worker) and demographic variables was run. Immigration status is found to be a significant explanatory variable for it determines the migrant's family location. Temporary workers tend to send proportionately higher income to the families they have left behind. Destination also matters for foreign income varies across destination, argued to be due to labor market segmentation.
Keywords: 330; Internationale Arbeitsmobilität; Rücküberweisung (Migranten); Schätzung; Philippinen